Language Week 2019 UiTM Seremban / Afni Anida Adnan - Adnan, Afni Anida (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2019)
There was a slight twist to ‘Language Week 2019’ for it was actually held for two weeks this time around. The idea for a two week Language Week was mooted as APB Seremban wanted to try out something new, especially with the first week coinciding with ‘Week Without Walls’. The activities were varied, and APB Seremban took the effort to cater to all aspects of students’ needs-physical, spiritual, mental and safety. The students’ artistic and creative talents too were honed and highlighted during these two weeks. The first week was filled with talks, inspirational and motivational besides informative. Amongst the talks given were a Fire and Safety Talk by En. Jamal Mawari from The Fire and Rescue Department of Negeri Sembilan, a talk on ‘Good Language on Social Media’ by Dr. Azmawaty Mohd Nor from University Malaya and a re-run of a pre-recorded Talk entitled ‘Dari Kelantan ke United Kingdom’ by Mr. Muhammad Afiq Ismail. The ‘Chinese Calligraphy and Arabic Khat’ and ‘Video Competion’ were also held during this week.